Crosstalk Between Autophagy and Innate Immunity: A Pivotal Role in Hepatic Fibrosis - Chen, Li; Kong, Desong; Xia, Siwei; Wang, Feixia; Li, Zhanghao; Zhang, Feng; Zheng, Shizhong (Frontiers in Pharmacology, 2022)
Liver fibrosis is a repair process of chronic liver injuries induced by toxic substances, pathogens, and inflammation, which exhibits feature as deposition of extracellular matrix. The initiation and progression of liver fibrosis heavily relies on excessive activation of hepatic stellate cells (HSCs). The activated HSCs express different kinds of chemokine receptors to further promote matrix remodulation. The long-term progression of liver fibrosis will contribute to dysfunction of liver and ultimately cause hepatocellular carcinoma. Liver also has abundant of innate immune cells, including DCs, NK cells, NKT cells, neutrophils, and Kupffer cells, which conduct complicated function to activation and expansion of HSCs and liver fibrosis. Autophagy is one specific type of cell death, by which the aberrantly expressed protein and damaged organelles are transferred to lysosomes for further degradation, playing a crucial role in cellular homeostasis. Autophagy is also important to innate immune cells in various aspects. The previous studies have shown that dysfunction of autophagy in hepatic immune cells can result in initiation and progression of inflammation in the liver, directly or indirectly causing activation of HSCs, which ultimately accelerate liver fibrosis. Given the crosstalk among innate immune cells, autophagy, and fibrosis progression are complicated, and the therapeutic options for liver fibrosis are quite limited, the exploration is essential. Herein, we review the previous studies about the influence of autophagy and innate immune on liver fibrosis and the molecular mechanism, to provide novel insight to prevention and treatment of liver fibrosis.